Photothermal catalytic material, preparation method and application thereof and Freon degradation method
By adopting photothermal catalytic materials with three-layer core-shell structures, the problems of high energy consumption and possible toxic by-products in the existing Freon degradation technology are solved, and efficient and stable degradation of gas-phase Freon is achieved, with good universality and multifunctional application potential.
Patent Information
- Application Number
- CN202411981836.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-03-25
AI Technical Summary
The existing Freon degradation technology has problems such as high energy consumption, complex equipment, and possible toxic by-products. Traditional photocatalysts are prone to deactivate during long-term use, and insufficient photothermal synergy.
Photothermal catalytic materials using three-layer core-shell structures include carbon-based material ball core, manganese oxide shell layer and graphene carbon nitride shell layer. By rationally designing the core-shell structure, the photothermal synergy effect is enhanced and the separation efficiency of photogenerated electrons and holes is improved.
It has achieved efficient and stable degradation of gas-phase Freon, reduced secondary pollution, and has good universality and multifunctional application potential. It is suitable for harmless treatment of harmful gases in the environmental protection field.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention relates to the field of photothermal catalysis and gas phase degradation of freon, in particular to a photothermal catalytic material, a preparation method and application thereof, and a freon degradation method. Background Art
[0002] There are many types of Freon (CFCs), which are generally gases at room temperature and pressure with a slight aromatic smell. They are transparent liquids at low temperatures or under pressure. They are miscible with halogenated hydrocarbons, monohydric alcohols and other organic solvents (such as oil, benzene, chloroform, etc.) in any proportion, and are also miscible with fluorine refrigerants. CFCs are widely used in many fields such as air conditioning, refrigeration equipment, sprays, foam plastics and electronic cleaning because they have the following physical and chemical properties: 1) They have strong chemical stability and are not easy to decompose; 2) They have good thermal stability and are non-flammable and non-explosive; 3) They are easy to change between gas and liquid phases; 4) They have low surface tension and are permeable; 5) They are non-toxic, non-irritating and non-corrosive; 6) They have high insulation properties; 7) They are appropriately hydrophilic; 8) They are cheap and easy to produce.
[0003] People use these properties of Freon in all aspects of life, which brings convenience to life, but also causes great harm to the environment. Scientific measurements show that Freon has a very strong ability to destroy the ozone layer and is one of the main causes of ozone layer depletion. The reduction of the ozone layer increases surface ultraviolet radiation, which seriously affects human health, such as causing skin cancer and cataracts, destroying the growth of crops, disturbing the ecological balance of the ocean, and even aggravating the aging of plastics and increasing photochemical air pollution. Therefore, how to effectively and environmentally friendly treat Freon has become an environmental problem that needs to be solved urgently.
[0004] Existing methods for harmless treatment of Freon include high temperature decomposition, radiation decomposition, catalytic hydrogenation and supercritical water, but these methods have many problems, such as high energy consumption, unsafe chemical reactions, harsh reaction conditions, difficult process control, high equipment cost, difficult batch processing and possible production of toxic byproducts. For example, high temperature decomposition and supercritical water treatment require high temperature and high pressure conditions, their equipment is complex and the system sealing requirements are very high, which not only consumes a lot of energy, but also has strict requirements on the sealing and high temperature and high pressure resistance of the equipment, resulting in very high operating costs of the entire process, complex equipment and difficult maintenance. Some existing catalytic methods (such as catalytic hydrogenation) may produce harmful intermediate byproducts during the degradation process, which not only increases the difficulty of treatment, but also may cause secondary pollution to the environment, which is obviously not ideal in the context of environmental protection and green sustainable development. Therefore, it is urgent to find an efficient, green and economically feasible Freon degradation technology and suitable catalysts.
[0005] In recent years, photothermal catalytic technology has been widely used in the degradation of various organic pollutants due to its environmental friendliness and high energy utilization. x ) shows high catalytic activity due to its multiple valence states and unique pore structure. It is often used for the catalytic degradation of various pollutants and is widely used in the fields of organic dyes, phenol, volatile organic pollutants, CO, flue gas combustion, etc. Graphite phase carbon nitride (g-C3N4) is also considered to be a material with good photocatalytic performance due to its narrow band gap (2.7 eV), excellent physicochemical stability, environmental friendliness and low cost. It can effectively absorb ultraviolet rays for electronic excitation. Core-shell structure catalysts can effectively protect the active sites of the reaction by coating active metals or compounds on the substrate, increasing the stability and reaction efficiency of the material. For example, it has been reported that a core-shell structure catalyst with titanium dioxide (TiO2) as the core and other metals or compounds coated on the surface is used for photocatalytic degradation of pollutants.
[0006] However, existing photocatalysts each have their own defects. For example, manganese oxide (MnO x ) has high oxidation activity as a catalyst, but when used independently, the particles are easy to agglomerate and the surface active sites are easy to deactivate, resulting in poor long-term stability of the catalyst, making it difficult to meet the requirements of long-term degradation of Freon. In addition, when manganese oxide is used alone as a catalyst, it is usually easy for particles to agglomerate in actual applications, resulting in a reduction in active sites, which makes the catalyst easy to lose activity during long-term use.
[0007] For example, although traditional g-C3N4 has certain photocatalytic performance, its light absorption band gap is narrow, the utilization rate of sunlight is insufficient; the inherent surface area is low, the light absorption capacity is limited; the quantum efficiency is low, resulting in rapid recombination of photogenerated carriers, which greatly reduces its photocatalytic efficiency. It has the disadvantages of insufficient utilization rate of sunlight and low quantum efficiency, which limits its performance in photothermal catalysis. In addition, the use of g-C3N4 alone as a catalyst is usually prone to particle agglomeration in practical applications, resulting in a reduction in active sites, which makes the catalyst easy to lose activity during long-term use.
[0008] In recent years, some researchers have improved the photocatalytic activity of g-C3N4 by doping metals in it or combining it with other photocatalytic materials. It has been used for the photocatalytic degradation of organic pollutants, but there are still deficiencies in the application of gas-phase Freon, especially in the photothermal synergy. In addition, there is little research on the photothermal synergistic degradation of core-shell structure catalysts, especially in the efficient degradation of Freon. There are still many technical barriers. In addition, many catalysts are effective for specific pollutants and lack adaptability and universality for multiple pollutants. Moreover, traditional Freon treatment methods generally have the problem of being effective only for specific compounds, and are usually not ideal when treating other volatile organic compounds (VOCs).
[0009] Therefore, combining different types of materials and leveraging synergistic effects to enhance their photothermal catalytic performance and achieve harmless photothermal catalytic treatment of Freon has become a key research direction. Summary of the invention
[0010] In view of this, the technical problem to be solved by the present invention is to provide a photothermal catalytic material, a preparation method and application thereof, and a Freon degradation method. The photothermal catalyst provided by the present invention has high degradation efficiency, strong universality, and has high degradation efficiency and stability for degrading gaseous Freon.
[0011] The present invention provides a photothermal catalytic material, comprising:
[0012] Carbon-based material ball core;
[0013] The manganese oxide shell layer coated on the surface of the carbon-based material ball core:
[0014] A g-C3N4 shell layer is coated on the surface of the manganese oxide shell layer.
[0015] In the photothermal catalytic material of the present invention, the mass ratio of the carbon-based material spherical core, the manganese oxide shell and the g-C3N4 shell is 1:(0.83~1):(0.04~0.36).
[0016] The photothermal catalytic material provided by the present invention comprises a carbon-based material ball (Carbon) core, a manganese oxide (MnO x ) middle layer and graphene carbon nitride (g-C3N4) outer shell layer constitute a three-layer core-shell structure spherical catalyst with excellent photothermal catalytic effect. Photothermal catalysis is a process that converts light energy into thermal energy and drives catalytic reactions by thermal energy. Photothermal catalytic materials generate heat after absorbing light energy, thereby accelerating chemical reactions.
[0017] The innermost layer is a carbon-based material ball, which as a core provides high conductivity and stability, thereby promoting the rapid transfer of photogenerated electrons. The carbon-based material ball core of the present invention is a carbon nanosphere core, a graphene ball core or a graphite carbon ball core.
[0018] The middle layer is a manganese oxide shell layer, which is coated on the core surface of the carbon-based material ball. The core layer formed by the combination of manganese oxide and the carbon-based material ball can not only significantly improve the migration efficiency of photogenerated carriers and reduce the recombination probability of electrons and holes, and enhance the overall efficiency of the photothermal catalyst, but also the formed core layer has high conductivity and excellent photothermal conversion ability, and can quickly convert the absorbed light energy into thermal energy.
[0019] The outermost layer is g-C3N4 nanosheets, which are coated on the surface of the manganese oxide shell layer. The coating of the outer layer of g-C3N4 forms a double shell structure. The outer shell coating of g-C3N4 effectively prevents the MnO x The agglomeration of particles increases the specific surface area and active sites of the material, enhances the photothermal catalytic performance of the catalyst, and enables it to exhibit higher efficiency and longer service life in the photothermal degradation of organic pollutants.
[0020] The three-layer structure composite design of the photothermal catalytic material described in the present invention enables the various materials to work synergistically with each other, enhance the photothermal synergistic effect, and improve the separation efficiency of photogenerated carriers, effectively inhibiting the recombination phenomenon of electrons and holes, thereby forming a photothermal catalytic material with high photothermal conversion efficiency and photogenerated electron separation capability.
[0021] The photothermal catalytic material of the present invention can also be coated with a SiO2 shell layer or an Al2O3 shell layer on the surface of the g-C3N4 shell layer. This multilayer structure can further increase the stability and chemical inertness of the material, prevent excessive reaction or deactivation of the catalyst, and enhance the long-term performance of the catalyst in harsh environments.
[0022] The present invention also provides a method for preparing the photothermal catalytic material described in any of the above technical solutions, comprising the following steps:
[0023] S1) adding permanganate dropwise into the carbon-based material ball suspension to mix, and calcining the obtained material to obtain a precursor;
[0024] S2) mixing the g-C3N4 sol and the precursor described in step S1), then removing the solvent, and calcining the material obtained after removing the solvent to obtain a photothermal catalytic material.
[0025] The present invention first adds permanganate dropwise to a suspension of carbon-based material balls and mixes, and calcines the obtained material to obtain a precursor. Specifically, the carbon-based material balls are ultrasonically dispersed in a solvent to obtain a uniformly dispersed suspension of carbon-based material balls, and permanganate is added dropwise to the carbon-based material ball suspension for mixing and stirring, and then centrifugation is performed. The obtained material after centrifugation is sequentially washed, dried and ground, and then calcined to obtain a precursor. The permanganate of the present invention is selected from one or more of potassium permanganate, sodium permanganate, calcium permanganate or barium permanganate. The solvent of the present invention is selected from anhydrous ethanol or deionized water, preferably anhydrous ethanol and deionized water in a volume ratio of 1: (14-16). The ultrasonic dispersion time of the present invention is 25 min-35 min; the mixing and stirring time is 1 h-2 h. The washing solution of the present invention includes deionized water. The drying temperature of the present invention is 70°C-90°C, preferably 80°C; the drying time is 10 h-13 h, preferably 11 h-12 h. The calcination temperature of the present invention is 550°C to 600°C, the calcination time is 2 h to 4 h, preferably 3 h, and the calcination heating rate is 2°C / min to 2.5°C / min. The molar ratio of the carbon-based material balls in the carbon-based material ball suspension of the present invention to the Mn ions in the permanganate is 1:(0.6~0.7). In certain embodiments of the present invention, the permanganate is potassium permanganate, and the mass ratio of the carbon-based material balls in the carbon-based material ball suspension to the potassium permanganate is 1:(8~9).
[0026] The carbon-based material balls of the present invention are selected from carbon nanospheres, graphene balls or graphite carbon balls. In certain embodiments of the present invention, the carbon-based material balls of the present invention are carbon nanospheres, which are prepared by the following method: dissolving glucose in a solvent and ultrasonically obtaining a transparent glucose solution, heating the transparent glucose solution at a constant temperature, centrifuging, washing, drying and grinding to obtain carbon nanospheres. The solvent of the present invention is selected from anhydrous ethanol or deionized water. The amount of glucose used in the present invention is 4 g~6g. The temperature of the constant temperature heating of the present invention is 160℃~180℃, and the reaction time is 6 h~8 h. The washing solution of the present invention is anhydrous ethanol. The drying temperature of the present invention is 70℃~90℃, preferably 80℃; the drying time is 10 h~13 h, preferably 11 h~12 h.
[0027] After obtaining the precursor, the present invention mixes the g-C3N4 sol with the precursor described in step S1), then removes the solvent, and calcines the material obtained after removing the solvent to obtain a photothermal catalytic material. Specifically, the obtained precursor is added to the g-C3N4 sol and mixed and stirred. After stirring for a certain period of time, the obtained mixed solution is dried to remove the solvent, and then the material obtained after removing the solvent is calcined under the protection of a protective gas to obtain a photothermal catalytic material. The amount of the precursor used in the present invention is 0.1 g~0.2 g, and the time for adding the obtained precursor to the g-C3N4 sol and mixing and stirring is 12 h~24 h. The temperature of calcining the material obtained after removing the solvent under the protection of a protective gas according to the present invention is 200°C~300°C, the calcination time is 3 h~5 h, preferably 4 h, and the heating rate is 2°C / min~2.5°C / min. The drying of the present invention is preferably freeze drying. The protective gas of the present invention is selected from one or more of nitrogen, helium, neon or argon, preferably nitrogen; the flow rate of the protective gas is 110 cm 3 / min~400 cm 3 / min.
[0028] The g-C3N4 sol of the present invention is obtained by heating g-C3N4 in a solvent; specifically, g-C3N4 is added to a solvent to obtain a suspension of g-C3N4, and the suspension is heated to obtain a transparent g-C3N4 sol. The solvent of the present invention is selected from anhydrous ethanol or deionized water. The amount of g-C3N4 used in the present invention is 0.05 g~0.45 g. The heating temperature of the present invention is 200℃~210℃, and the heating time is 6 h~8 h. The hydrothermal method cuts the block g-C3N4 into nanosheet small molecules, which is safer and more convenient than the dangerous reagents used in other methods.
[0029] The preparation method of the photothermal catalytic material provided by the present invention comprises the following steps: hydrothermal method is used to synthesize carbon-based material balls, MnO x Modified carbon-based material spheres (Carbon@MnO x ) and g-C3N4 coated Carbon@MnO x The preparation method is green and simple, with low energy consumption. It adopts a green process combining low-temperature calcination with a hydrothermal method. The raw materials involved, such as glucose, g-C3N4 and potassium permanganate, are relatively cheap and readily available. The designed preparation process minimizes the impact on the environment. The entire process is carried out under relatively mild conditions, which has the advantages of low cost and environmental protection, thereby greatly reducing energy consumption and cost, and is particularly suitable for large-scale industrial applications. By optimizing the preparation process and reasonably selecting materials, the present invention realizes the preparation of core-shell Carbon@MnO under mild conditions. x@g-C3N4 catalyst, the final composite material has good catalytic activity and stability.
[0030] The present invention also provides the use of the photothermal catalytic material described in any of the above technical solutions or the photothermal catalytic material obtained by the preparation method described in any of the above technical solutions in the preparation of an organic pollutant degradation catalyst. In particular, the photothermal catalytic material provided by the present invention degrades gas phase Freon under simulated sunlight conditions, exhibits significant photothermal catalytic degradation ability, can effectively degrade Freon and reduce secondary pollution, and is suitable for harmless treatment of harmful gases in the field of environmental protection. Traditional treatment technologies for Freon, such as high temperature decomposition and supercritical water treatment, usually require high energy consumption and high cost equipment support. These technologies not only have high energy consumption, but also may produce toxic by-products, causing secondary pollution to the environment. The present invention uses the above photothermal catalytic material as a Freon degradation catalyst, which not only has good catalytic activity and stability, but also does not produce toxic by-products. The photothermal degradation process mainly uses sunlight as energy, which greatly reduces dependence on traditional energy. Compared with traditional treatment methods such as high temperature pyrolysis, the present invention can achieve effective degradation of Freon at a lower energy input, has higher environmental friendliness and economic feasibility, and avoids high energy consumption and complex high temperature and high pressure equipment in traditional treatment methods.
[0031] In addition, the photothermal catalytic material provided by the present invention not only has a significant photothermal degradation effect on Freon, but can also be extended to treat other types of volatile organic compounds (VOCs), such as toluene, benzene, xylene and other organic pollutants. The same core-shell catalyst structure can adapt to a variety of pollutants, and by selectively adjusting the MnO x The ratio of g-C3N4 to g-C3N4 can optimize its degradation performance for specific pollutants. The photothermal catalytic material of the present invention can also be applied to the degradation of liquid phase pollutants (such as organic dyes, phenol compounds, etc.). It can effectively catalyze the degradation of organic pollutants in water bodies through photothermal action and realize liquid phase environmental remediation, showing good universality and multifunctional application potential.
[0032] In particular, the present invention provides a method for degrading freon, comprising the following steps:
[0033] Under light radiation, the freon and the freon degradation catalyst are reacted;
[0034] The Freon degradation catalyst is the photothermal catalytic material described in any of the above technical solutions or the photothermal catalytic material obtained by the preparation method described in any of the above technical solutions.
[0035] In certain embodiments of the present invention, the following steps are included: under light radiation, the freon and the balance gas are passed through a freon degradation catalyst for reaction; the flow rate of the freon and the balance gas is 80 mL / min to 120 mL / min, preferably 100 mL / min; the space velocity is 55000 mL / g·h to 65000 mL / g·h, preferably 60000 mL / g·h. The present invention can use nitrogen as the balance gas. In addition to using nitrogen as the balance gas, an inert gas (such as argon) can also be used to control the reaction atmosphere, and even photocatalytic degradation can be carried out in an oxygen environment, thereby further improving the photocatalytic degradation rate and oxidation capacity.
[0036] In some embodiments of the present invention, the optical power density of the optical radiation of the present invention is 300 mW / m 2 ~400mW / m 2 , preferably 350 mW / m 2 In certain embodiments of the present invention, the concentration of the Freon of the present invention is 150 ppm to 250 ppm, preferably 200 ppm; the amount of the Freon degradation catalyst is 75 mg to 125 mg, preferably 100 mg.
[0037] When the present invention performs photothermal degradation of Freon, the light radiation source may use different types of light sources such as LED lamps, ultraviolet lamps, and visible light lamps in addition to using xenon lamps to simulate sunlight. The basis for selecting the light source may be the light absorption characteristics of the pollutants and the optimal light absorption wavelength range of the catalyst.
[0038] The present invention provides a photothermal catalytic material, a preparation method and application thereof, and a Freon degradation method. The photothermal catalytic material provided by the present invention effectively solves the recombination problem of photogenerated carriers through its three-layer composite design. The synergistic effect of the core-shell structure enables the material to exhibit higher photothermal conversion efficiency and photocatalytic activity during photothermal catalytic degradation of Freon, effectively improving the separation efficiency of photogenerated electrons and holes and reducing the recombination probability. Specifically, the present invention rationally designs the core-shell structure, the high conductivity of the Carbon core and the MnO x The photothermal conversion function of g-C3N4 works together to greatly improve the photocatalytic effect of g-C3N4. This three-layer composite design forms a structure that can maximize the photothermal synergistic effect, making the efficiency of the present invention in photothermal catalytic degradation of Freon under simulated sunlight conditions significantly higher than that of the single material in the prior art. In addition, the present invention adopts a double coating design of the core-shell structure, Carbon@MnO xThe core and the outer layer g-C3N4 work together to effectively prevent the agglomeration of catalyst particles, significantly increase the specific surface area and catalytic active sites of the material, and enable the catalyst to maintain high activity and long-term stability in the degradation reaction, and can continuously and effectively degrade Freon. The catalyst of the present invention exhibits high catalytic activity for Freon and other gaseous pollutants, indicating that it has good universality and can be adapted to treat a variety of volatile organic pollutants (VOCs), especially when treating mixed emissions of multiple pollutants. It is particularly effective and has broader prospects in the field of environmental governance. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 This is a scanning electron microscope image of CMCN-0.05 in Example 2;
[0040] Figure 2 This is the electron microscope image of CMCN-0.35 in Example 2;
[0041] Figure 3 This is an electron microscope image of the CMCN-0.45 photothermal catalyst in Example 2;
[0042] Figure 4 The fluorescence (PL) spectra of the CMCN composite materials with different mass ratios and pure g-C3N4 in Example 2;
[0043] Figure 5 The ultraviolet diffuse reflectance (UV-vis) spectra of the CMCN composite materials with different mass ratios in Example 2;
[0044] Figure 6 X-ray diffraction (XRD) diagrams of CMCN composite materials with different mass ratios in Example 2;
[0045] Figure 7 is the infrared (FTIR) spectra of the CMCN composite materials with different mass ratios in Example 2;
[0046] Figure 8 X-ray diffraction (XRD) diagrams of CMCN composite materials with different mass ratios in Example 2;
[0047] Fig. 9 This is a graph showing the results of tetrafluoroethane degradation stability test of the CMCN-0.35 composite material obtained in Example 2;
[0048] Fig.10 The temperature variation curve of CMCN composite materials with different mass ratios and pure g-C3N4 over time in Example 2;
[0049] Fig.11 This is the instantaneous temperature infrared imaging of CMCN-0.35 and pure g-C3N4 during the catalytic process. DETAILED DESCRIPTION
[0050] The present invention discloses a photothermal catalytic material, a preparation method and application thereof, and a Freon degradation method. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve it. It is particularly important to point out that all similar substitutions and modifications are obvious to those skilled in the art, and they are all considered to be included in the present invention. The method and application of the present invention have been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the method and application of this article without departing from the content, spirit and scope of the present invention to realize and apply the technology of the present invention.
[0051] The present invention will be further described below in conjunction with embodiments:
[0052] Example 1
[0053] This example provides a carbon nanosphere precursor modified by manganese oxide (C@MnO x The preparation method comprises the following steps:
[0054] (1) Synthesis of uniformly dispersed carbon nanospheres by hydrothermal method: 4 g of glucose was dissolved in a mixed solution of 30 mL of deionized water and 2 mL of ethanol and ultrasonicated for 30 min. The ultrasonicated solution was placed in 50 mL of polytetrafluoroethylene and moved into a constant temperature box and reacted at 170 °C for 6 h. After cooling naturally to room temperature, the product was collected by centrifugation, cleaned by three cycles of centrifugation, washing, and redispersion in water and alcohol, and dried at 80 °C for 12 h, and ground to obtain a brown powder.
[0055] (2) 0.125 g of potassium permanganate was dissolved in 50 mL of deionized water to form a purple solution, and then 0.15 g of carbon nanospheres was added to 50 mL of deionized water and ultrasonicated for 30 min to form a uniformly dispersed slurry. The potassium permanganate solution was added dropwise to the carbon sphere slurry and stirred at room temperature for 1 h. The resulting slurry from each sample was then washed three times with water and then centrifuged. The solid was dried at 80 °C for 12 h. The product C@MnO was obtained by grinding. x .
[0056] (3) The product was placed in a tube furnace and calcined at 550 °C for 3 h under N2 protection with a temperature increase gradient of 2.1 °C / min to obtain C@MnO x Precursor.
[0057] Example 2
[0058] This embodiment provides C@MnO wrapped by g-C3N4 with different masses x The preparation method of the double-core-shell photothermal catalyst of the precursor comprises the following steps:
[0059] (1) 10 g of dicyandiamide was placed in a crucible in the constant temperature zone of a muffle furnace and heated from 30 °C to 550 °C at a heating rate of 2.3 °C / min. The calcination temperature was maintained for 4 h and the product was naturally cooled to room temperature to obtain a light yellow block product. The product was fully ground and set aside for later use. The yield was 40%.
[0060] (2) Synthesis of Carbon@MnO by sol-gel assisted calcination x @g-C3N4: 0.005 g, 0.015 g, 0.025 g, 0.035 g and 0.045 g of g-C3N4 were respectively suspended in 20 mL of deionized water, and the suspension was poured into a polytetrafluoroethylene autoclave and moved into a thermostat at 210 °C for 6 h. After cooling naturally to room temperature, 0.1 g C@MnO x The precursor was stirred at room temperature for 24 h and freeze-dried to remove the solvent to obtain Carbon@MnO x @g-C3N4 precursor.
[0061] (3) The Carbon@MnOx@g-C3N4 precursor was calcined at 200 °C for 4 h in a tube furnace under N2 protection with a temperature ramp of 2.1 °C / min to obtain a series of final products CMCN-X (X = 0.05, 0.15, 0.25, 0.35, 0.45, X represents g-C3N4 and core Carbon@MnOx@g-C3N4). x The corresponding materials are named CMCN-0.05, CMCN-0.15, CMCN-0.25, CMCN-0.35, and CMCN-0.45, among which the scanning electron microscopy images of CMCN-0.05, CMCN-0.35, and CMCN-0.45 photothermal catalysts are shown in Figures 1 to 3 As shown, Figure 1 This is a scanning electron microscope image of CMCN-0.05 in Example 2. Figure 2 This is the electron microscope image of CMCN-0.35 in Example 2. Figure 3 This is an electron microscope image of the CMCN-0.45 photothermal catalyst in Example 2.
[0062] Fluorescence tests were performed on the CMCN composite materials with different mass ratios obtained in Example 2 and pure g-C3N4. The results are as follows: Figure 4 As shown, Figure 4 The fluorescence (PL) spectra of the CMCN composite materials with different mass ratios and pure g-C3N4 in Example 2. The PL spectrum can be used to detect the recombination efficiency of photogenerated electrons and holes in the material. Low fluorescence intensity usually indicates a lower recombination rate, which is beneficial to the improvement of catalytic performance.
[0063] The CMCN composite materials with different mass ratios obtained in Example 2 and pure g-C3N4 were tested for UV diffuse reflection. The results are as follows: Figure 5 As shown, Figure 5 The UV-vis spectra of the CMCN composite materials with different mass ratios in Example 2 are shown. The UV-vis spectra are a method for analyzing the light absorption characteristics of materials and are used to evaluate the absorption capacity of catalysts to light of different wavelengths in order to understand their light-to-heat conversion characteristics.
[0064] X-ray diffraction tests were performed on the CMCN composite materials with different mass ratios obtained in Example 2 and pure g-C3N4. The results are as follows: Figure 6 As shown, Figure 6 The X-ray diffraction (XRD) diagrams of the CMCN composite materials with different mass ratios in Example 2 are used to analyze the crystal structure of the CMCN composite materials. The crystal phase information and crystal properties of the samples can be read out. By adjusting the amount of raw materials, the rules can be observed.
[0065] The CMCN composite materials with different mass ratios obtained in Example 2 and pure g-C3N4 were subjected to infrared (FTIR) spectroscopy test. The results are as follows: Figure 7 As shown, Figure 7 The infrared (FTIR) spectra of the CMCN composite materials with different mass ratios in Example 2 can be used to analyze the detection of chemical bonds and functional groups of the CMCN composite materials.
[0066] Example 3
[0067] Evaluation of photothermal catalytic oxidation activity: Tetrafluoroethane was used as the degradation object to explore the degradation activity of tetrafluoroethane under different mass ratio catalysts under solar irradiation over time. The photothermal catalytic oxidation of tetrafluoroethane was carried out in a fixed bed flow quartz tube reactor equipped with a quartz glass window. Tetrafluoroethane was introduced into the reaction chamber through a gas flow rate control system and was in full contact with the photothermal catalyst placed in the reaction chamber. The xenon lamp CEL-HXF300 xenon lamp light source of Beijing Zhongjiao Jinyuan Technology Co., Ltd. was used. The xenon lamp light source was irradiated onto the catalyst through the quartz glass window. The test conditions were: tetrafluoroethane concentration was 200 ppm, catalyst dosage was 100 mg, and reaction light power density was 350 mW / m 2 , the reaction flow rate was controlled at 100mL / min, the space velocity was 60000mL / g·h, N2 was the balance gas; the CO2 concentration was detected online by gas chromatograph. (The degradation substance tetrafluoroethane in this experiment belongs to the freon derivative hydrofluorocarbons (HFCs), which can represent freon)
[0068] The catalytic performance of tetrafluoroethane was tested on the CMCN composite materials with different mass ratios and pure g-C3N4 obtained in Example 2. The results are as follows: Figure 8 As shown, Figure 8The X-ray diffraction (XRD) diagrams of CMCN composite materials with different mass ratios in Example 2, where Blank represents a blank control. The results show that compared with pure g-C3N4, the CMCN composite materials all exhibit significant photothermal catalytic activity, and the tetrafluoroethane conversion rate of CMCN-0.35 can reach 87.42% in 120 min.
[0069] The CMCN-0.35 composite material obtained in Example 2 was subjected to tetrafluoroethane degradation stability test. The results are as follows: Fig. 9 As shown, Fig. 9 This is a graph showing the results of a tetrafluoroethane degradation stability test on the CMCN-0.35 composite material obtained in Example 2. Fig. 9 It was demonstrated that the CMCN-0.35 composite material can still maintain a high catalytic activity after multiple photothermal catalytic degradation of tetrafluoroethane, indicating its excellent stability and ability to be reused.
[0070] The CMCN composite materials with different mass ratios obtained in Example 2 and pure g-C3N4 were tested for the change in temperature over time during the catalytic process (specifically, the instantaneous temperature change on the catalyst surface after light irradiation during the reaction, which can reflect that the CMCN composite material can be converted into heat energy after light irradiation and has an excellent photothermal conversion effect). The results are as follows Fig.10 and Fig.11 As shown, Fig.10 The temperature variation curve of CMCN composite materials with different mass ratios and pure g-C3N4 over time in Example 2 is shown in FIG. Fig.11 The instantaneous temperature infrared imaging diagram of CMCN-0.35 and pure g-C3N4 during the catalytic process shows that the temperature of the CMCN composite material rises rapidly after light irradiation due to the thermal effect of carbon nanospheres and the confinement effect of the core-shell structure, indicating that the excellent performance of the CMCN composite material of the present invention comes from its core-shell structure.
[0071] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A photothermal catalytic material, characterized in that: include: Carbon-based material ball core; The manganese oxide shell layer coated on the surface of the carbon-based material ball core: A g-C3N4 shell layer is coated on the surface of the manganese oxide shell layer.
2. The photothermal catalytic material according to claim 1, characterized in that: The mass ratio of the carbon-based material ball core, the manganese oxide shell and the g-C3N4 shell is 1:(0.83~1):(0.04~0.36).
3. The photothermal catalytic material according to claim 1, characterized in that: The carbon-based material ball core is a carbon nanoball core, a graphene ball core or a graphite carbon ball core.
4. The photothermal catalytic material according to claim 1, characterized in that: It also includes a SiO2 shell layer or an Al2O3 shell layer coated on the surface of the g-C3N4 shell layer.
5. The method for preparing the photothermal catalytic material according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1) adding permanganate dropwise into the carbon-based material ball suspension to mix, and calcining the obtained material to obtain a precursor; S2) mixing the g-C3N4 sol and the precursor described in step S1), then removing the solvent, and calcining the material obtained after removing the solvent to obtain a photothermal catalytic material.
6. The method for preparing a photothermal catalytic material according to claim 5, characterized in that: In step S1), the molar ratio of the carbon-based material balls in the carbon-based material ball suspension to the Mn ions in the permanganate is 1:(0.6-0.7); In step S2), the mass ratio of the g-C3N4 sol to the precursor is (0.05~0.45):
1.
7. The method for preparing a photothermal catalytic material according to claim 5, characterized in that: In step S2), the g-C3N4 sol is obtained by heating g-C3N4 in a solvent; The heating temperature is 200° C. to 210° C., and the heating time is 6 h to 8 h.
8. The method for preparing a photothermal catalytic material according to claim 5, characterized in that: In step S1), the calcination temperature is 550°C to 600°C, and the calcination time is 2 h to 4 h; In step S2), the calcination temperature is 200° C. to 300° C., and the calcination time is 3 h to 5 h.
9. Use of the photothermal catalytic material described in any one of claims 1 to 4 or the photothermal catalytic material obtained by the preparation method described in any one of claims 5 to 8 in the preparation of an organic pollutant degradation catalyst.
10. A method for degrading freon, characterized in that: The following steps are involved: Under light radiation, the freon and the freon degradation catalyst are reacted; The Freon degradation catalyst is the photothermal catalytic material described in any one of claims 1 to 4 or the photothermal catalytic material obtained by the preparation method described in any one of claims 5 to 8.
Citation Information
Cited By
Core-shell structure catalyst as well as preparation method and application thereof
CN120550794A